High strength epoxy system modified with soft block copolymer and stiff core-shell rubber nanoparticles: Morphology, mechanical properties, and fracture mechanisms - A. Bajpai; B. Wetzel; K. Friedrich (eXPRESS Polymer Letters)
The tensile and thermo-mechanical properties, as well as the fracture mechanical behavior of a high strength epoxy/amine system modified with particulates of a block copolymer (BCP), a core shell rubber (CSR) and a mixture of them, were investigated at 23 °C. The results show that the fracture energy was increased by more than 700% with a filler content of 12 wt% BCP and by more than 600% with a filler content of 12 wt% CSR particles. The content of BCP and CSR particles influences the final morphology and, thus, also the tensile properties, fracture toughness and thermo-mechanical behavior of the modified systems. The toughening mechanisms induced by the BCP and CSR particles were identified as (a) localized plastic shear yielding around the particles and (b) cavitation of the particles followed by plastic void growth of the epoxy polymer. The fracture toughness and fracture energy were co-related to the plastic zone size for all systems modified. These mechanisms were modeled using the Hsieh et al. [45] approach which also allows calculating the values of GIc of the differently modified polymers. Excellent agreement was found between the predictions and the experimentally measured fracture energies.